Career Trajectory, Aspiring Deans - John Buckwalter; Sheila Pineres; Kelli Brown (Academic Chairpersons Conference Proceedings, 2016)
While higher educational institutions have well developed processes to assist faculty as they progress through their academic careers, most colleges and universities provide little formal assistance to department heads and chairs considering career progression to a deanship. This interactive session will provide practical guidance in an interactive format to those contemplating pursuing an academic dean position.
Keywords: practical guidance to those contemplating pursuing an academic dean position